PREVALENCE OF FUNGAL IN OPPORTUNISTIC INFECTION HIV TYPE-1 IN SUBURBAN, KADAPA - Obulesu, Gundala; Ar, Hanumanthapp; E, Prabakar Reddy (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Isolate fungal element causing in opportunistic infection of human immunodeficiency virus and correlated with CD4 cell counts. Methods: Different samples are used and media: Sabouraud dextrose agar, using mycological methods such as potassium hydroxide, lactophenol cotton blue mount, India ink preparation, and Gram-staining. Results: Both bacterial and fungal isolates were obtained from 8 cases. Pneumococci and Candida spp. were observed in 3 cases followed by Staphylococcus aureus and Aspergillus in 2 cases, Klebsiella pneumoniae and Geotrichum spp., Pneumococci and Penicillium spp., and Acinetobacter baumannii, and Cryptococcus spp. from 1 case each. Only fungal isolates were obtained from 6 cases of sputum samples. Candida spp. (50%) were predominant fungal isolate followed by Aspergillus spp. (33.33%) and Cryptococcus spp. (16.66%). Cryptococcus spp. was the predominant fungal isolate (66.6%) followed by Candida pseudotropicalis (Kefyr) in 16.66% (1/6) and Acinetobacter spp. was isolated from 16.66 % (1/6). Conclusion: Respiratory infections were the predominant manifestations comprising chronic bronchitis, pneumonia, chronic obstructive pulmonary disease, and chronic cough. 66 individuals were with respiratory symptoms, of them 28 individuals had CD4 count 50-200/mm3, 22 had CD4 <50/mm3.